Cardiopulmonary phenotype associated with human PHD2 mutation. Issue 7 (10th April 2017) - Talbot, Nick P.; Smith, Thomas G.; Balanos, George M.; Dorrington, Keith L.; Maxwell, Patrick H.; Robbins, Peter A.
Abstract: Oxygen‐dependent regulation of the erythropoietin gene is mediated by the hypoxia‐inducible factor (HIF) family of transcription factors. When oxygen is plentiful, HIF undergoes hydroxylation by a family of oxygen‐dependent prolyl hydroxylase domain (PHD) proteins, promoting its association with the von Hippel‐Lindau (VHL) ubiquitin E3 ligase and subsequent proteosomal degradation. When oxygen is scarce, the PHD enzymes are inactivated, leading to HIF accumulation and upregulation not only of erythropoietin expression, but also the expression of hundreds of other genes, including those coordinating cardiovascular and ventilatory adaptation to hypoxia. Nevertheless, despite the identification of over 50 mutations in the PHD‐HIF‐VHL pathway in patients with previously unexplained congenital erythrocytosis, there are very few reports of associated cardiopulmonary abnormalities. We now report exaggerated pulmonary vascular and ventilatory responses to acute hypoxia in a 35‐year‐old man with erythrocytosis secondary to heterozygous mutation in PHD2, the most abundant of the PHD isoforms. We compare this phenotype with that reported in patients with the archetypal disorder of cellular oxygen sensing, Chuvash polycythemia, and discuss the possible clinical implications of our findings, particularly in the light of the emerging role for small molecule PHD inhibitors in clinical practice. Abstract : The hypoxia‐inducible factor (HIF) transcriptional pathway regulates the expression of hundreds of genes, which collectively control hematopoietic, cardiovascular and respiratory adaptations to hypoxia. However, although mutations in HIF and associated proteins have now been described in many patients with previously unexplained congenital erythrocytosis, there are relatively few reports of abnormal cardiopulmonary phenotypes in such patients. In this case report, we describe exaggerated ventilatory and pulmonary vascular responses to hypoxia in a young patient with a mutation in the PHD2 gene, which encodes a key oxygen sensor within the HIF pathway. We compare our findings with previous reports, and discuss their potential clinical significance.